Allogeneic hematopoietic stem cell transplantation for Crohn disease complicated with myelodysplastic syndrome: A case report. Issue 10 (March 2020) - Zhang, Ying; Lou, Li-Li; Shi, Xiao-Dong; Lu, Sha-Sha; Zhang, Li-Xia; Huang, Xu; Ji, Hui-Fan; Li, Xu; Guo, Xiao-Lin
Abstract: Rationale: Myelodysplastic syndrome (MDS) can be complicated with Crohn disease (CD). Irritable bowel disease (IBD) associated with MDS has already been reported in the past; however, hematopoietic stem cell transplantation (HSCT) is rarely performed. Herein, we report a case of CD with MDS for HSCT. Patient concerns: A 41-year-old man was hospitalized due to abdominal pain and intermittent fever for 40 days. Two years later, he was readmitted due to abdominal pain and diarrhea with fever for 10 days. Diagnosis: Symptoms, laboratory examinations, and imaging findings of the patient were indicative of CD complicated with MDS. Interventions: An allogeneic HSCT was performed. Outcomes: He died of severe lung infection 125 days post-transplantation. Lessons: The number of cases of CD combined with MDS remains insufficient, and no consensus opinions are available to date. Hence, HSCT is a very potential treatment method. Additional experiences are needed to determine its effectiveness.